RESEARCH OF ALPHA-PARTICLE TRANSFER REACTIONS - Sailaubekov Е.Қ.; Morzabayev А.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This paper presents the capabilities of nuclear physics for the development of nuclear cluster physics. Frequencies of several nucleons, acting as component clusters, are one of the key aspects of the nuclear device. Therefore, the basis for the clustering was helium nuclei (α-particles). This article explores the different types of cluster ensembles and different types of unmanaged nuclei as the fundamental components of new quantum environments. The experimental results of the α-particle transfer reactions under the complete synthesis of some of the cluster nuclei show the formula for those reactions. Specifically, this work focuses on the so-called "cluster nucleus model" - a model that describes the excited states of the nuclei, ie helium nuclei. One of the most important goals of this work is to carefully analyze the author’s available data on research of alpha-particle reactions and to compare them with today’s promising models of nuclei, to identify and explain new patterns. The author of the article received experimental data from various publications in journal articles and "personal contact". Relevant sources in the article have reference to sources.